Analysis of Exclusive Breastfeeding Factors for Infants in Gogagoman Village - Strahmawati Hamzah (Universitas Mandala Waluya, 2021)
WHO stated that 53% of cases were recorded as acute pneumonia, 55% of cases were recorded as deaths due to diarrhea, this was because the mother did not exclusively breastfeed. In Indonesia, the coverage rate of breastfeeding is still quite low, only 54,3%. The purpose of this study was to analyze the factors associated with exclusive breastfeeding in Gogagoman Village. This type of research is an analytic observational with a cross sectional study approach. The number of samples in this study were 122 mothers with simple random sampling technique, data were collected using a questionnaire through interviews and analyzed using the chi square test (α = 0,05). The results showed that there was a relationship between maternal knowledge p-value = 0.012, there was a relationship with maternal attitudes p-value = 0,000, there was a relationship with family support p-value = 0,005, there was a relationship between support for health workers, p-value = 0,000, and there was a relationship between promotion of formula milk p-value = 0,000 with exclusive breastfeeding for babies. In conclusion, the factors related to exclusive breastfeeding for babies in Gogagoman Village are knowledge, attitudes, family support, support for health workers and promotion of formula milk.